Pengaruh Kompetensi, Objektivitas, Etika, Integritas, dan Time Budget Pressure terhadap Kualitas Pemeriksaan pada BPK Perwakilan Kalimantan Timur - Firmansyah Firmansyah; Sarwani Sarwani; Lili Safrida (Universitas Winaya Mukti, 2020)
This study aims to determine the effect of competence, objectivity, ethics, integrity, and time budget pressure on audit quality. Compliance with applicable accounting standards to maintain public trust in high state institutions in the Audit Board of the Republic of Indonesia is needed. This research was conducted at the Audit Board of the Republic of Indonesia, East Kalimantan Province Representative. Data were taken from distributed questionnaires, and produced 35 respondents using purposive sampling technique. The method of data analysis in this study used multiple linear regression. The results of this study indicated that integrity had a positive effect on audit quality. It showed that the higher the integrity of an auditor, the better the quality of the resulting inspection or auditing, while the variables of competence, objectivity, ethics, and time budget pressure had no effect on the quality of the resulting audit quality.